BEBERAPA PERSPEKTIF TENTANG MENGELOLA PERUBAHAN DAN INOVASI DI SEKOLAH - Moh. Zamili (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2014)
In everyday, the phenomenon of life is always changing, humans also changed. But why when people are in an organization, they tend to be difficult to accept changes? In fact, man is composed of organs (body) but created a different tune. The main problem of the human reluctance to change is the perception (research Bruhn et.al.,) and interpersonal communication (research Peter Senge). If these two issues are able to be harmonized, undoubtedly the capable organizations innovate to achieve the desired quality